Hydrodynamically mediated breakup of droplets in microchannels - Che, Zhizhao (2012)
A flow focusing junction is integrated into a microchannel to break up droplets into a controllable number and size of daughter droplets. High speed images of the breakup at the flow focusing junction show that the breakup depends on the interplay between interfacial tension, shear force on the interface, and the confinement of the microchannel. Phase diagrams of the splitting performance show that the breakup is controllable by varying the flow rate of the continuous phase or by varying the size of the mother droplet.